AR (q, v) Modeling of Normal Lung Sounds - Vanderschoot, J.; Schreur, H. J. W. (Methods of Information in Medicine, 1994)
A model for the dependence of normal lung sounds upon airflow and air volume recorded at the mouth, is proposed and investigated. Data from 8 healthy subjects and 2 sessions have been analysed. Test statistics give very strong support for the adequacy of the model. This opens possibilities for diagnostic application of the model to normal lung sounds. Several suggestions are given for still further improvement of the model.
Keywords: Lung Sounds; Autoregressive Modeling